Supporting Cognition With Modern Technology: Distributed Cognition Today and in an AI-Enhanced Future - Grinschgl, Sandra; Neubauer, Aljoscha C. (Frontiers in Artificial Intelligence, 2022)
—Due to the reviewers suggestions we added some additional, important information to the abstract, thus it now sightly exceeds the word limit. As we think that this additional information is important we refrained from shortening the abstract, however we could still to so if necessary.—